Jahn-Teller effects in molecules on surfaces with specific application to C_60 - Hands, Ian D.; Dunn, Janette L.; Rawlinson, Catherine S.A.; Bates, Colin A. (Springer-Verlag, 2010)
Scanning tunnelling microscopy (STM) is capable of imaging molecules adsorbed onto surfaces with su±cient resolution as to permit intramolecular features to be discerned. Therefore, imaging molecules subject to the Jahn-Teller (JT) effect could, in principle, yield valuable information about the vibronic coupling responsible for the JT effect. However, such an application is not without its complications. For example, the JT effect causes subtle, dynamic distortions of the molecule; but how will this dynamic picture be affected by the host surface? And what will actually be imaged by the rather slow STM technique? Our aim here is to present a systematic investigation of the complications inherent in JT-related STM studies, to seek out possible JT signatures in such images and to guide further imaging towards identifcation and quantifcation of JT effects in molecules on surfaces. In particular, we consider the case of surface-adsorbed C60 ions because of their propensity to exhibit JT effects, their STM-friendly size and because a better understanding of the vibronic effects within these ions may be important for realisation of their potential application as superconductors.